2015
DOI: 10.1097/aog.0000000000000858
|View full text |Cite
|
Sign up to set email alerts
|

Donor Death After Selective Fetoscopic Laser Surgery for Twin–Twin Transfusion Syndrome

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 24 publications
3
45
1
Order By: Relevance
“…The preoperative finding of umbilical artery AREDF in TTTS donors can be considered as a sign of severe hypovolemia, placental insufficiency, or both . The coexistence of severe FGR was found to be an additional risk factor of donor's demise in previous studies . Our data showed that, among donors surviving at 1 week after laser treatment, the incidence of FGR was similarly high in the group with Doppler normalization and in cases with persistently abnormal findings (Table ), and that in 68% of growth restricted donors with prelaser Doppler abnormalities, there was normalization after treatment, suggesting a hypovolemic cause of preoperative findings in these cases more than a hypoxic mechanism.…”
Section: Discussionsupporting
confidence: 56%
“…The preoperative finding of umbilical artery AREDF in TTTS donors can be considered as a sign of severe hypovolemia, placental insufficiency, or both . The coexistence of severe FGR was found to be an additional risk factor of donor's demise in previous studies . Our data showed that, among donors surviving at 1 week after laser treatment, the incidence of FGR was similarly high in the group with Doppler normalization and in cases with persistently abnormal findings (Table ), and that in 68% of growth restricted donors with prelaser Doppler abnormalities, there was normalization after treatment, suggesting a hypovolemic cause of preoperative findings in these cases more than a hypoxic mechanism.…”
Section: Discussionsupporting
confidence: 56%
“…An elevated MCA‐PSV in the donor almost doubled the risk of demise, but this finding did not reach significance (OR 1.91, 95% CI, 0.97‐3.76). Three studies reported the odds of donor demise for AEDF and REDF in the UA separately . All three studies concluded that REDF in the UA was the strongest predictor of donor demise.…”
Section: Resultsmentioning
confidence: 99%
“…It reflects both placental insufficiency (maldevelopment and unequal sharing) and fetal hypotension secondary to the hemodynamic imbalance in TTTS. Three studies showed that REDF in the UA is a stronger predictor of donor IUFD than AEDF . It is suggested that reversed UA flow reflects placental insufficiency in a greater degree and that it is not amenable to improvement following restoration of volume status .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In TTTS, donor demise is more common than recipient demise following FLP. Several risk factors for postprocedure donor fetal demise have been identified, including fetal growth discordance greater than 30%, reverse end‐diastolic velocity in the donor umbilical artery, marginal or velamentous cord insertion, or increased number of anastomoses …”
Section: Introductionmentioning
confidence: 99%